A Dual-Strategy Approach: The Role of Muroja’ah and Tasmi’ in Sustaining Qur’an Memorization Quality - Nur Kholis; Zunaidah Zunaidah (Al-Qalam Institute, 2026)
Sustaining the quality of Qur’an memorization requires systematic strategies beyond routine repetition. This study aims to analyze how structured Muroja’ah and tasmi’ strategies contribute to memorization durability, accuracy, accountability, and stability. Using a qualitative case study design, data were collected from students and Tahfiz teachers through in-depth interviews, non-participant observations during recitation sessions, and document analysis of memorization control books and evaluation sheets. The findings indicate that structured Muroja’ah strengthens long-term retention as students report reduced forgetting and more stable recall, while tasmi’ sessions improve tajwid accuracy and increase performative responsibility through direct correction and monitored recitation. Documentation records demonstrate consistent weekly progress and systematic monitoring, confirming strategy integration. The novelty of this study lies in conceptualizing these traditional practices as an integrated quality assurance model. It is recommended that Tahfiz institutions implement structured monitoring systems to ensure sustainable memorization outcomes.